CARA MEMBUAT DATA KOORDINAT DIJITAL DARI AREA PENAMBANGAN BATU SPLIT YANG BERSUMBER DARI DATA THEODOLITH KONVENSIONAL - Jarwanto (Nusantara Hasana Berdikari, 2022)
Sokkisha's conventional Theodolith units can be used for land mapping, but the results can be digitized according to the current software format. The data obtained are data on azimuth direction, optical distance, elevation which are recorded manually and processed using Microsoft Excel software. The results obtained are data that have x, y and z coordinates and are then supplemented with data that has: number, easting (